Kepemimpinan Kiai dalam Mengembangkan Pendidikan Berbasis Karakter di Pesantren al Urwatul Wutsqo Jombang - Mashur Mashur (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2017)
Characters is pillars of nation building, moral decadence happened can be overcome by character-based education. The existence of pesantren which mission is preaching Islam has advantages as educational institutions which not only improves the quality of science, but develop and cultivate students' character, because education is based on and driven by the values ​​of Islam. Kiai is a scholar who has task to edify the pupils as the Prophet task, he is also as a central figure in pesantren, whether or not the pesantren develope, depends entirely on the leadership of kiai. The result of the study about the role of kiai the first, he is as initiators, framers, originator and designer patterns of development, curriculum author, being the type of leadership is rational Sufi, charismatic and paternalistic spiritual. Second, the pattern of development of character-based education model patterns of internal and exsteren development. Third, the method of character education by teaching methods (At Ta'lim), methods of habituation (At Ta'wiid), and Qudwah methods. Fourth, inhibiting and supporters Factors.